A Flow Approach to Industrial Sites, Firm Dynamics and Regional Employment Growth: A Case Study to Amsterdam-North - Cees Gorter; Frank Bruinsma; Peter Nijkamp (Tinbergen Institute, 1998)
This paper analyses the relationship between spatial dynamics offirms and employment growth in the region. Moreover, it addresses thefacilitating or impeding role of (new) industrial sites in thegeographical process of firm and job dynamics, while recognising thatthe spatial dynamics of firms reflect socio-economic developments atboth the regional and national level.To this end, a novel conceptual theoretical-framework based on theflow approach, is developed, through which the relationship betweenspatial dynamics of firms (entries, exits, and relocations)and changes in regional employment (job creation and job destruction)can be systematically analysed. Moreover, it also allows to assessthe generative employment effects of firm moves from and to (newlycreated) industrial sites in the region. To demonstrate in practicethe usefulness of this new approach for the regional employmenteffects of spatial firm dynamics (facilitated or hindered byindustrial site developments), an empirical application to the areaof Amsterdam-North (The Netherlands) will be presented.
Keywords: 330; Gewerbegebiet; Betriebliche Standortwahl; Erwerbstätigkeit; Amsterdam